Limited Self-Control, Obesity and the Loss of Happiness - Alois Stutzer; Armando N. Meier (Center for Research in Economics, Management and the Arts (CREMA), 2015)
Is obesity the consequence of an optimally chosen lifestyle or do people consume too much relative to their long-term preferences? The latter perspective accepts that people might face self-control problems when exposed to the immediate gratification from food. We exploit unique survey data for Switzerland in multinomial logit and ordered probit regressions to study i) the covariates of obesity including indicators of self-control, and ii) the consequences of obesity on the subjective well-being of people with limited willpower. Our main finding is that obesity decreases the well-being of individuals who report having limited self-control, but not otherwise.
Keywords: D12; D91; I12; I31; 330; obesity; revealed preference; self-control problem; subjective well-being